2021
DOI: 10.3389/fimmu.2021.628364
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus miR-US33as-5p Targets IFNAR1 to Achieve Immune Evasion During Both Lytic and Latent Infection

Abstract: As the first line of antiviral defense, type I interferon (IFN) binds IFN receptor 1 (IFNAR1) and IFNAR2 to activate the Jak-STAT signal transduction pathway, producing IFN-stimulated genes (ISGs) to control viral infection. The mechanisms by which human cytomegalovirus (HCMV) counteracts the IFN pathway are only partially defined. We show that miR-US33as-5p encoded by HCMV is expressed in both lytic and latent infection. By analysis with RNA hybrid and screening with luciferase reporter assays, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…It therefore serves as a m ure of MMP, such that mitochondrial oxidative phosphorylation uncouplers suc FCCP, which disrupts ATP synthesis by depolarising mitochondrial membrane pote cause dye dispersal and loss of TMRE fluorescence (Figure 1A-C, and reviewed in [2 To investigate the protective function of β2.7 during latent infection, we moc fected, or infected CD14+ monocytes with wild type (WT) virus or virus with a β2.7 deletion (Δβ2.7) in the Toledo strain of HCMV. Monocytes infected with HCMV known to undergo latent infection which can be maintained in long-term culture [5, 1 32] and the Toledo strain of HCMV has been shown to undergo latent infection in my progenitor cells [33][34][35][36][37]. Fourteen days post infection (d.p.i), cells were either treate mock-treated with cadmium chloride for 24 h, and then TMRE and Hoechst stained expected, the addition of cadmium chloride to mock infected cells caused a severe in the number of cells with visible TMRE staining, indicating mitochondrial depola tion (Figure 2A,B).…”
Section: β27 Protects Against Mitochondrial Stress In Infected Monocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…It therefore serves as a m ure of MMP, such that mitochondrial oxidative phosphorylation uncouplers suc FCCP, which disrupts ATP synthesis by depolarising mitochondrial membrane pote cause dye dispersal and loss of TMRE fluorescence (Figure 1A-C, and reviewed in [2 To investigate the protective function of β2.7 during latent infection, we moc fected, or infected CD14+ monocytes with wild type (WT) virus or virus with a β2.7 deletion (Δβ2.7) in the Toledo strain of HCMV. Monocytes infected with HCMV known to undergo latent infection which can be maintained in long-term culture [5, 1 32] and the Toledo strain of HCMV has been shown to undergo latent infection in my progenitor cells [33][34][35][36][37]. Fourteen days post infection (d.p.i), cells were either treate mock-treated with cadmium chloride for 24 h, and then TMRE and Hoechst stained expected, the addition of cadmium chloride to mock infected cells caused a severe in the number of cells with visible TMRE staining, indicating mitochondrial depola tion (Figure 2A,B).…”
Section: β27 Protects Against Mitochondrial Stress In Infected Monocytesmentioning
confidence: 99%
“…By contrast, monocytes infected with WT virus were partially tected from this cadmium-induced loss of TMRE staining, but this protection was lo To investigate the protective function of β2.7 during latent infection, we mock infected, or infected CD14+ monocytes with wild type (WT) virus or virus with a β2.7 gene deletion (∆β2.7) in the Toledo strain of HCMV. Monocytes infected with HCMV are known to undergo latent infection which can be maintained in long-term culture [5,11,[28][29][30][31][32] and the Toledo strain of HCMV has been shown to undergo latent infection in myeloid progenitor cells [33][34][35][36][37]. Fourteen days post infection (d.p.i), cells were either treated or mock-treated with cadmium chloride for 24 h, and then TMRE and Hoechst stained.…”
Section: β27 Protects Against Mitochondrial Stress In Infected Monocytesmentioning
confidence: 99%
“…RANTES is also a chemokine that induces the proliferation and activation of NK cells with the help of T cells to release particular cytokines (IL-2 and IFN-γ) [105]. The latest study showed that HCMV-miR-US33as-5p binds the 3 -UTR of IFN receptor 1 (IFNAR1) and interferes with the typical IFN signaling pathway to limit the release of IFN-stimulated genes (ISGs), which can encode antiviral proteins [68].…”
Section: Hcmv-encoded Mirnas Regulate Biological Functions Of Host Immune Cellsmentioning
confidence: 99%
“…Besides that, miR-US25-1-5p evaded innate antiviral immunity by regulating Cyclophilin A-CD147-ERK/NF-κB pathway targeting CD147 ( Chen et al, 2017 ). miR-US33as-5p downregulated the expression of IFN-stimulated genes (ISGs), inhibited STAT1 translocation into the nucleus, and subsequently evaded the immune system’s killing ( Zhang et al, 2021 ). Moreover, in clinical research, miR-US5-2-3p increased T-cell responses and HCMV reactivation in renal transplant recipients ( Waters et al, 2020 ).…”
Section: The Roles Of Aberrant Expression Of Human Cytomegalovirus-in...mentioning
confidence: 99%